ANALISIS STRATEGI PUBLIC RELATIONS POLLUX HABIBIE MEISTERSTADT DALAM MEMBANGUN CITRA PERUSAHAAN - Mira Rahmadhany; Sholihul Abidin (LPPM Universitas Putera Batam, 2024)
The construction of Pollux Habibie Meisterstadt in Batam has caused significant flooding issues affecting the local community. This development disrupts natural water flow patterns, drainage systems, and the land's capacity to absorb rainwater, exacerbated by the addition of impermeable surfaces such as concrete and asphalt. Criticism of the Environmental Impact Assessment (EIA) for its lack of comprehensiveness highlights the need for thorough evaluation. The role of Public Relations (PR) is crucial in managing this crisis by handling communication and public perception, and preparing effective crisis communication plans. PR strategies implemented include publications, events, and community relations, involving fact-finding, planning, communication, and continuous evaluation. This qualitative descriptive study indicates that comprehensive and transparent PR strategies, along with collaboration with government and technical experts, are essential in restoring public trust and building a positive corporate image. Key Words: Strategy, Public Relation, Image